1879 Terr. of Mont. Laws 359 - (:unkn) unknown (My University, 1879)
Ch. 4, § 23: Prohibited dueling and killing a person involved with a rifle, shot-gun, pistol, Bowie knife, dirk, small-sword, back-sword, or other dangerous weapon. Punishable by death by hanging.
Keywords: DUELING